'Hermann Heller and the European Crisis: Authoritarian Liberalism Redux?'. Issue 3 (12th February 2015) - Scheuerman, William E.
Abstract This essay tentatively buttresses Alexander Somek's view that Hermann Heller's 1933 essay, 'Authoritarian Liberalism', provides a useful starting point for thinking about the ongoing European crisis, in which European authorities are favouring rigid austerity and pro‐business policies while undermining basic liberal and democratic rights. Heller's unfortunate neglect, especially in Anglophone scholarship, is discussed. Nonetheless, Somek and other recent scholars who have turned to Heller to make sense of the European crisis downplay some of the tough questions raised by any attempt to apply Heller's analysis of the Weimar crisis to the contemporary setting. In particular, Heller's theory relied on a robust social democratic statism which has become increasingly unpopular even among theorists on the political left.